1982
DOI: 10.1111/j.1365-2672.1982.tb04375.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and toxin formation by Clostridium botulinum at low pH values

Abstract: Spores of Clostridium botulinum were found to initiate growth and to produce toxin in aqueous suspensions of soya protein at pH values as low as 4‐2 and in skimmed milk at pH 4.4. Most of the experiments were done with mixed cultures of CI. botulinum types A and B in the presence of two strains of Bacillus subtilis. The role of the latter organism was concluded to be to lower the oxygen content and the Eh of the suspensions. Toxin was produced at pH 4‐4 after 4 weeks of incubation at 30oC when either hydrochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…In terms of pH value, the mascarpone cheese can be recognised as a medium that is favourable for microbiological growth. In general, the pathogens do not grow, or grow very slowly, at pH levels below 4.6 (Smelt et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In terms of pH value, the mascarpone cheese can be recognised as a medium that is favourable for microbiological growth. In general, the pathogens do not grow, or grow very slowly, at pH levels below 4.6 (Smelt et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Waterman and Small (1998) showed the survival on beef particles of acid‐sensitive bacteria such as Salmonella typhimurium , Shigella flexneri and Escherichia coli and suggested that ground beef could raise the pH of the acidified medium in the microenvironment of the bacteria. Growth of, and toxin production by, Clostridium botulinum at pH 4·3 required proteins from skimmed milk or soya (Smelt et al. 1982).…”
Section: Discussionmentioning
confidence: 99%
“…For example, acetic acid is recognized as a better inhibitor (at similar pH) of bacterial growth than other acids used in food preservation. The minimum pH required to inhibit growth and toxin production by Clostridium botulinum depends on the acid used (Minor and Marth, 1972;Smelt et al, 1982). Similarly Sorrels et al (1989) reported that overall antimicrobial action (i.e.…”
Section: Water Activity Conceptmentioning
confidence: 97%